Molecular Genotyping of Toxoplasma gondii in Human Spontaneous Aborted Fetuses in Shiraz, Southern Iran. - Qasem Asgari; Maysam Fekri; Ahmad Monabati; Mohsen Kalantary; Iraj Mohammadpour; Mohammad Hossein Motazedian; Bahador Sarkari (Tehran University of Medical Sciences, 2013)
Congenital toxoplasmosis is associated with variable complications including encephalitis, microcephaly, hydrocephaly, hepatitis, lymphadenopathy and even intrauterine death. Presence of Toxoplasma gondii in human placenta may induce congenital infection. The aim of this study was to determine the genotypes of Toxoplasma gondii infection in human spontaneous aborted fetuses in Shiraz, south of Iran.Five hundred and forty two paraffin-embedded blocks of aborted placenta were collected, from two university-affiliated hospitals in Shiraz. Occurrence of spontaneous abortion was confirmed by examine of the slides. After re-cutting of the blocks and dewaxing, semi-nested PCR assay was used to detect the fragments of T. gondii B1 gene in the samples. Also direct molecular genotyping was performed on positive samples with Restriction Fragment Length Polymorphism-PCR analysis on the SAG2 gene.Among the 542 tissue samples, the B1 gene was amplified from 78 (14.4%) of cases with the semi nested PCR and typed by RFLP. The genotype of Toxoplasma strains of 65 (out of 78) PCR-positive samples were evaluated and 54 out of 65 (83.1%) were found to be type II and 11 out of 65 (16.9%) were type I.Considering the high level of Toxoplasma infection in aborted fetuses in this study, Toxoplasma might largely contribute to spontaneous abortion in this area of Iran.